The impact of board attributes on financial performance of South African companies - Marokane, Tshepo Terence (My University, 2016)
Empirical evidence has established that companies with robust corporate governance systems outperform their counterparts who do not have such structures in place (Ehikioya, 2009). A critical component of a strong corporate governance system is a board of directors (Hermalin & Weisbach, 2001). Through its King reports, South Africa has a developed code of governance principles (West, 2006). The latest such report, King III, mandatory for all companies listed on the Johannesburg Stock Exchange (JSE), is clear about board attributes such as size, independence and diversity (Gstraunthaler, 2010). The aim of this study is to investigate the impact of board attributes on the financial performance of JSE-listed companies. The contradictory results from international studies on the topic (Pereira & Filipe, 2014), as well as the limited empirical evidence for the South African-specific context (Collins G Ntim, Opong, Danbolt, & Thomas, 2012), prompted this study The results are based on a Pearson Correlation test evaluating how board attributes impact companies' financial performance. Further tests, such as regression models, could have been used, and indeed this was so in previous studies (Nguyen, Locke, & Reddy, 2014; Austin Ujunwa, Okoyeuzu, & Nwakoby, 2012). However, the results obtained from the Pearson Correlation test did not justify a need for further analyses, and in fact the number of variables selected could have eroded the accuracy of the findings. The chosen variables for board attributes are as follows: size, independence and diversity. Operating Profit (OP), Return on Assets (ROA) and Return on Equity (ROE ) were the selected dependent variables to measure company financial performance. When the variables were tested, the only statistically significant relationship was established with ROE, which correlated with board size and non-white directors only. OP and ROA did not have a significant correlation with any of the board attributes.
MBA
Keywords: Corporate governance -- South Africa. Boards of directors -- South Africa. Industrial management -- South Africa.